2019
DOI: 10.1155/2019/5258493
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Computerised Cognitive Training of Everyday Cognition in Parkinson’s Disease

Abstract: Objectives. We piloted a computerised cognitive training battery in a group of participants with Parkinson’s disease without dementia to investigate the relevance of the training to daily life and the feasibility and the acceptability of the tasks. Previous studies of CT have had limited success in the benefits of training, extending to improvements in everyday function. By taking a pragmatic approach and targeting training to the cognitive skills affected by Parkinson’s disease (planning, attention, and recol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Our findings are consistent with recent evidence presented by Cuevas et al [91] suggesting individuals with T2DM may be motivated to participate in cognitive activities due to their concerns of developing dementia. The programme format was found to be acceptable in the current study, and in line with previous research [92,93], cognitive training was found to be challenging but enjoyable. Enjoyment is a key determinant of intervention acceptability and has been directly linked to increased adherence and long-term compliance to positive health behaviours [94][95][96][97].…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are consistent with recent evidence presented by Cuevas et al [91] suggesting individuals with T2DM may be motivated to participate in cognitive activities due to their concerns of developing dementia. The programme format was found to be acceptable in the current study, and in line with previous research [92,93], cognitive training was found to be challenging but enjoyable. Enjoyment is a key determinant of intervention acceptability and has been directly linked to increased adherence and long-term compliance to positive health behaviours [94][95][96][97].…”
Section: Discussionsupporting
confidence: 86%
“…This study therefore expands on previous research in several ways. First, we note that this study tested a much larger sample size ( n = 53) than previous experiments that examined visuospatial training in adults (which had samples ranging from n = 4 to 15) (Cerasa et al 2014 ; Folkerts et al 2018 ; Smith et al 2019 ; Tippett and Rizkalla 2014 ). Second, exploratory analyses also indicated that within the training group, more improvement on the CBTT was associated with more improvement on the mental rotation test.…”
Section: Discussionmentioning
confidence: 99%
“…Computerized training programs that do selectively target visuospatial ability have shown efficacy in younger children in improving mental rotation (Cheung et al 2020 ; Rodan et al 2019 ) and visuospatial working memory (Gizzonio et al 2022 ). Visuospatial-specific training for adults has also been beneficial, but it has only been piloted in small samples (i.e., n ≤ 15) (Cerasa et al 2014 ; Folkerts et al 2018 ; Smith et al 2019 ; Tippett and Rizkalla 2014 ). Although most cognitive interventions span multiple days, there is evidence of improvement in visuospatial scores from a single session (Sanchez 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…23 The theoretical premise behind CCT is that it can stimulate neuroplasticity. 24 From a neuropsychological perspective, 25 CCT has the potential to shape brain structure and reorganize function among cognitively healthy older adults [26][27][28] and individuals with Alzheimer disease, 29,30 Parkinson disease, 31,32 attention deficits, 33 and acquired brain injury. 34 Furthermore, physiological parameters, including brain metabolism 35 and inflammatory, 36 hormonal, 37 and sleep-related factors, 38 may also be transformed through brain plasticity.…”
Section: Introductionmentioning
confidence: 99%